Role of Laser Suture Lysis in Immediate Trabeculectomy Failure - Safdar Ali Abbasi, Dure Yakta Shaikh, Syed Imtiaz Ali Shah, Shujaat Ali Shah, Partab Rai Shahid Jamal Siddiqui (Pakistan Journal of Ophthalmology, 2015)
Purpose: To study the role of laser suture lysis in immediate trabeculectomy failure. Material and Methods: This was a prospective case series study conducted at Department of Ophthalmology, Chandka Medical College Hospital Larkana, Pakistan from May 2007 to May 2015. 21 eyes of 20 patients who underwent trabeculectomy for primary open angle glaucoma and encountered immediate trabeculectomy failure were included in the study. Immediate trabeculectomy failure was considered when IOP during first 48 hours after trabeculectomy remained above 25 mm Hg. Laser suture lysis was carried out with Nd: YAG Laser (1064 nm) or with frequency doubled Nd: YAG Laser (532 nm). The preprocedure and post-procedure IOP was noted and IOP below 18 mm Hg was considered as successful laser suture lysis. Data entry and analysis was done on SPSS version 20. Results: 12 (60 %) patients out of the total 20 patients were males and 8 (40 %) were females. The mean age ± standard deviation of patients was 61.45 ± 7.37 years and the age range was 47 to 71 years. IOP came down to normal in all the cases after the laser suture lysis, without encountering any major complications. Mean IOP before laser suture lysis was 30.95 ± 2.20 mm Hg and mean IOP one hour after successful laser suture lysis was 13.38 ± 1.53 mm Hg. Conclusion: Laser suture lysis is a safe, effective and day care procedure in the management of immediate trabeculectomy failure. Keywords: Glaucoma, Trabeculectomy, failure, laser, suture.